New Technologies in Marketing as Competitive Advantage (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2018)
The goal of this paper is to outline the effect of new technologies in marketing on competitive advantage of the company. Sophisticated technology is drastically changing the society including consumer behaviour and their purchasing patterns. Many companies are already actively combining IoT technology, mobile applications, smart home appliances and other consumer electronics devices in multiple marketing communication channels. Marketing Managers are increasingly starting to direct company's communication towards modern marketing channels such as mobile and online with traditional channels slowly being replaced. New technologies in retail marketing, such as NFC and Bluetooth LE, offer a wide range of opportunities for reaching consumers in various creative ways. Soon, integrated multi-channel marketing strategies will include a seamless flow of personalized brand's messages through a number of inter-connected channels. Methodology used in this paper includes study of scientific articles and literature on marketing, YouTube videos and secondary online research. The conclusion of the paper is that mobile marketing is able to provide consumers unique brand experience, greater real-time interaction, greater brand recognition which will result in higher customer loyalty. By recognizing the value of new technologies in marketing and by implementing them, companies can achieve strong competitive advantage and a greater return on investment.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.